Decoding mitochondrial DNA damage and repair associated with H. pylori infection - Shahi, Aashirwad; Kidane, Dawit (Frontiers in Cellular and Infection Microbiology, 2025)
Mitochondrial genomic stability is critical to prevent various human inflammatory diseases. Bacterial infection significantly increases oxidative stress, driving mitochondrial genomic instability and initiating inflammatory human disease. Oxidative DNA base damage is predominantly repaired by base excision repair (BER) in the nucleus (nBER) as well as in the mitochondria (mtBER). In this review, we summarize the molecular mechanisms of spontaneous and H. pylori infection-associated oxidative mtDNA damage, mtDNA replication stress, and its impact on innate immune signaling. Additionally, we discuss how mutations located on mitochondria targeting sequence (MTS) of BER genes may contribute to mtDNA genome instability and innate immune signaling activation. Overall, the review summarizes evidence to understand the dynamics of mitochondria genome and the impact of mtBER in innate immune response during H. pylori-associated pathological outcomes.